Parties and the power of capital intensive under open-list proportional representation system: The case of Indonesia - Al-Hamdi, Ridho (Masyarakat, Kebudayaan dan Politik, 2024)
Since the Indonesian election adopted the Open-List Proportional Representation (OLPR) system in 2009 until the present, most political parties have altered their campaign strategies in the parliamentary election. The ownership of capital intensive is seemingly a certainty for political parties if they wish to succeed in the electoral match. Therefore, this article is aimed to demonstrate that capital intensive has a powerful impact in regard to the party triumph in the electoral arena under an OLPR system. It can be seen with the successful experience of four political parties in Indonesia, namely the Gerindra Party (Great Indonesia Movement), PKB (National Awakening Party), the Nasdem Party (National Democrat), and PKS (Prosperous Justice Party) in two elections, 2014 and 2019. Methodologically, it is qualitative research by utilizing in-depth interviews and online news gathering as the data collection technique. With the usage of four marketing-mix indicators (product, price, place, promotion), the article findings revealed that most political parties generally had uniformity in those four indicators despite different ideologies, programs, and strategies. Each party respectively required financial costs, an ideological platform, past achievements, popular candidate profile, physiological costs, local networks, direct campaign strategies to voters, elite approaches, and tactical promotions through mass media. Thus, this study concludes that these costs, which are referred to as “capital intensive,” determine the party’s victory in achieving electoral success.